Mixed Reversible Covalent Crosslink Kinetics Enable Precise, Hierarchical Mechanical Tuning of Hydrogel Networks. Issue 19 (15th March 2017) - Yesilyurt, Volkan; Ayoob, Andrew M.; Appel, Eric A.; Borenstein, Jeffrey T.; Langer, Robert; Anderson, Daniel G.
Abstract : Hydrogels play a central role in a number of medical applications and new research aims to engineer their mechanical properties to improve their capacity to mimic the functional dynamics of native tissues. This study shows hierarchical mechanical tuning of hydrogel networks by utilizing mixtures of kinetically distinct reversible covalent crosslinks. A methodology is described to precisely tune stress relaxation in PEG networks formed from mixtures of two different phenylboronic acid derivatives with unique diol complexation rates, 4‐carboxyphenylboronic acid, and o ‐aminomethylphenylboronic acid. Gel relaxation time and the mechanical response to dynamic shear are exquisitely controlled by the relative concentrations of the phenylboronic acid derivatives. The differences observed in the crossover frequencies corresponding to p K a differences in the phenylboronic acid derivatives directly connect the molecular kinetics of the reversible crosslinks to the macroscopic dynamic mechanical behavior. Mechanical tuning by mixing reversible covalent crosslinking kinetics is found to be independent of other attributes of network architecture, such as molecular weight between crosslinks. Abstract : Hydrogels from multiple, kinetically distinct, reversible covalent crosslinks enable precise tuning of relaxation and self‐healing times. Relaxation time is sensitive to the relative concentration of slow versus fast crosslinks in the network, and is also sensitive to pH. Orthogonal tuning of response timescale and strength of the elastic response is demonstrated by varying the molecular weight between crosslinks.